2019
DOI: 10.1159/000497314
|View full text |Cite
|
Sign up to set email alerts
|

Novel Association between <b><i>Flavin-Containing Monooxygenase 3</i></b> Gene Polymorphism and Antithyroid Drug-Induced Agranulocytosis in the Han Population

Abstract: Some effective antithyroid drugs (ATDs) have been widely used for patients with Graves’ disease (GD) but are associated with ATD-induced agranulocytosis. We selected 29 ATD-induced agranulocytosis patients, 44 ATD-induced neutropenia patients, and 140 GD controls among the Chinese Han population who were recruited at the First Affiliated Hospital of Xi’an Jiao Tong University. We assessed their response to ATDs treatment by performing genotyping for a candidate gene association study of samples from patients r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Although c.769G>A [p.(Val257Met)] has little effect on FMO3-catalyzed S-oxygenation of methimazole in vitro (Dolphin et al, 2000), the variant is associated with antithyroid (methimazole) drug-induced agranulocytosis in Han Chinese being treated for Graves' disease (He et al, 2019). The results suggest that the variant, which is common in this population, would be a useful predictor of antithyroid drug-induced agranulocytosis in Chinese patients undergoing methimazole treatment of hyperthyroidism.…”
Section: Effects On Drug Metabolismmentioning
confidence: 90%
“…Although c.769G>A [p.(Val257Met)] has little effect on FMO3-catalyzed S-oxygenation of methimazole in vitro (Dolphin et al, 2000), the variant is associated with antithyroid (methimazole) drug-induced agranulocytosis in Han Chinese being treated for Graves' disease (He et al, 2019). The results suggest that the variant, which is common in this population, would be a useful predictor of antithyroid drug-induced agranulocytosis in Chinese patients undergoing methimazole treatment of hyperthyroidism.…”
Section: Effects On Drug Metabolismmentioning
confidence: 90%
“…Peripheral blood samples were collected, and DNA was extracted using a genomic DNA Kit (Tiangen Biotech Co., Ltd.). MICA‐129 genotyping was performed using the iPLEX MassARRAY system as previously reported 35 . Then, genotyping for the MICA‐STR variant was performed according to a fluorescent‐based method in which primers were labelled at the 5′ end with the fluorescent reagent 6‐HEX.…”
Section: Methodsmentioning
confidence: 99%
“…MICA-129 genotyping was performed using the iPLEX MassARRAY system as previously reported. 35 Then, genotyping for the MICA-STR variant was performed according to a fluorescent-based method in which primers were labelled at the 5′ end with the fluorescent reagent 6-HEX. Polymerase chain reaction (PCR) fragments were generated using primers (MICA5 F, 5′-CTTTTTTTCAGGGAAAGTG-3′; MICA5 R, 5′-CCTTACCATCTCCAGAAACTGC-3′) that flank the STR polymorphism in the TM region of the MICA gene.…”
Section: Genotyping Of Mica-str and Mica-129 Genetic Variantsmentioning
confidence: 99%
“…Studies by Park et al (13) and Sung et al (14) demonstrated that the SnPs c.855c>T and c.472G>a affected the pharmacokinetics of sulindac in women who underwent preterm labor. Febrile neutropenia, myelosuppression and agranulocytosis related to these SnPs have also been reported previously (25,29,30). considering the relatively high frequency of FMO3 genetic polymorphisms in the population, the functional defects in FMo3 enzymes associated with these SnPs may have notable clinical implications, such as the variations in drug exposure followed by toxicity or delayed elimination of toxic substances.…”
Section: Discussionmentioning
confidence: 54%
“…FMO3 also affects the levels of several clinically important medications, and its polymorphisms are associated with drug toxicity ( 25 , 29 , 30 ). The c.923A>G SNP has been shown to increase voriconazole concentrations by reducing FMO3 enzyme activity ( 25 ), while c.855C>T SNP can increase the concentration of teneligliptin ( 6 ).…”
Section: Discussionmentioning
confidence: 99%